Radiation detriment estimation: on the possibility of effective dose usage to assess the number of years of the healthy life lost - L. V. Repin (Радиационная гигиена)
The Russian Law “On Radiation Safety of the Population” defines the effective dose as “the amount of exposure to ionizing radiation used as a measure of the risk of long-term consequences of human’s body exposure…” In turn, the Russian “Radiation Safety Standards” (RSS 99/2009) establish a procedure for assessing the health risk, associated with exposure to low doses, for two types of harmful effects (oncological diseases and hereditary effects) and two age and sex groups (“whole population” and “adults”) by multiplying corresponding linear risk coefficients per effective dose. At the same time, these documents do not impose restrictions on the risk assessment procedure, without excluding the use of any other risk indicators or risk assessment for other sex and age groups of the population. The value of radiation detriment to health, calculated by the method described in RSS 99/2009 to characterize the risk, as a unit of measurement, uses the fatal oncological disease caused by exposure to ionizing radiation, weighted by the number of years of life lost, or weighted by the severity of non-fatal cancer. Currently, mortality-based health measures are considered insufficiently informative characteristics of the impact of external factors on population health. Such indicators are poorly suited for a comparative analysis of risks, especially taking into account the different distribution of negative consequences over time. The paper presents an applied approach to expand the application of the radiation risk assessment methodology, without making significant changes to the established practice of radiation protection. The possibility of using the DALY value (disability-adjusted life years) as an measure of radiation risk is being considered; the expediency of changing approaches to calculating the effective dose (by using different values of weighting factors for tissues and organs during effective dose calculation for different age and sex groups of the population) and the possible scope of the proposed approaches to risk assessment in practice are discussed; an approach is proposed for calculating the DALY value using the effective dose and the corresponding risk factors (DALY×Sv-1).